Evaluation of a radial flux air-cored permanent magnet machine drive with manual transmission drivetrain for electric vehicles - Groenewald, David Jordaan (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.